Active learning fosters financial behavior: Experimental evidence - Tim Kaiser; Lukas Menkhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
We conduct a randomized field experiment to study the effects of two financial education interventions offered to small-scale retailers in Western Uganda. The treatments contrast "active learning" with "traditional lecturing" within standardized lesson-plans. We find that active learning has a positive and economically meaningful impact on savings and investment outcomes, in contrast to insignificant impacts of lecturing. These results are not conditional on prior education or financial literacy. The active learning intervention seems to be superior as it works via three cognitive and non-cognitive mechanisms, i.e. increased financial knowledge, self-control, and financial confidence, while lecturing only affects financial confidence.
Keywords: O16; D14; I21; 330; financial behavior; financial literacy; active learning; lecturing; training method; field experiment